Bioinspired orientation-regulated conductive hydrogels with hierarchical lamellar architecture for synergistic mechanical and electrical robustness - Tianhao Yu; Chao Rong; Ting Su; Shijia Wan; Bowei Zhang; Yabin Yan; Fu-Zhen Xuan (Chemical Engineering Journal, 2026)

Anomalously low winter sea surface temperatures during the holocene thermal maximum: A novel proxy from the Northern South China Sea - Yiping Yang; Rong Xiang; Fuchang Zhong; Lanlan Zhang; Sui Wan; Wubiao Li (Global and Planetary Change, 2026)

Reliable quantification and efficient purification of osteopontin from bovine milk using anion-exchange and membrane chromatography - Xinru Zuo; Shuai Ren; Jinrui Du; Yimeng Li; Muran Ma; Lu Tao; Yinzi Cui; Rong Fan; Yuhong Mao; Guoqiang Chen; Caiyun Wang; Yinhua Wan; et al. (Food Chemistry, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

Natural organic matter concentration controls the coordination and redox interaction between cerium ions and manganese oxides - Aling Wan; Bei Liu; Meng Zhang; Weiwen Chen; Iso Christl; Mengxia Wang; Xinyu Rong; Yufei Shu; Zhongying Wang (Journal of Hazardous Materials, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Environmental eustress inhibits CCL2 to overcome doxorubicin-induced cardiotoxicity and alleviate tumor growth - Peiyuan Bai; Chaobao Liu; Ao Liu; Zehao Zhuang; Jinghong Zhang; Lu Tang; Naifu Wan; Runda Wu; Wuwei Rong; Siqin Chen; Jinglei Wan; Yang Yang; et al. (Science Bulletin, 2026)

Differential Enrichment of Deep Shale Gas in Southeastern Sichuan Basin: Dynamic Evolution and Preservation Mechanisms - Ke Zhang; Haikuan Nie; Songhang Zhang; Tianwu Xu; Zhujiang Liu; Chuanxiang Sun; Chengxiang Wan; Wei Dang; Pei Li; Jia Rong; Shuheng Tang (Journal of Earth Science, 2026)

Role of GPCR41 silencing in conjugated linoleic acid-induced adipogenesis of bovine intramuscular preadipocytes - Rong Wan; Chuanfang Zhang; Qingxiang Meng; Siwei Nong; Zhenming Zhou (In Vitro Cellular & Developmental Biology - Animal, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Structural characterization and anti-aging mechanism of Codonopsis pilosula polysaccharides - Meiqi Wan; Rong Han; Xiaoai Bao; Yizheng Sun; Hailong Xu; Yanlin Wang; Aihong Zhao; Youbo Zhang (Food Research International, 2026)

Methionine-driven covalent chelation of Zn2+ by linusorb: a paradigm in hydrophobic cyclic peptide metal binding - Yi-kang Zhang; Du-jian Deng; Zhong-yi Luo; Wan-nan Wang; Jun-le Li; Shao-rong Zhang; Jia-li Li; Jia-zi Chen; Yong Wang; Zi-zhe Cai (Food Chemistry, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Global patterns and soil controls governing terrestrial nitrogen cycling in response to experimental warming: A meta-analysis - Sen-Mao Zhang; Wan-Jia Hu; Xin-Rong Shi; Robert L. Kallenbach; Zhi-You Yuan (Soil Biology and Biochemistry, 2026)

Microwave treatment enhances brown rice edible quality: Deciphering moisture content-driven modulation of microstructure, moisture distribution and starch properties - Yang Yu; Jiayu Zhang; Dan Ouyang; Rong He; Kai Huang; Shangyuan Sang; Yanan Liu; Jiali Xing; Ying Wan; Xiaohu Luo (Journal of Cereal Science, 2026)

Mechanism of synergistic astringency enhancement by organic acids in model wine: Insights from organic acid-phenols-protein triadic interaction - Yan Liu; Xiang Jie Jiang; Shi qing Zhang; Qing hao Zhao; Yue fan Zhao; Wan Rong Zhao; Shi Yi Peng; Guo Rong Du; Xiao Yuan; Peng Tao Zhao; Xiao Yu Wang (Food Chemistry, 2026)

Automatic Detection of Disaster-Causing Organisms near the Waters of Nuclear Power Plant Based on LiveScope Scanning Sonar Images - Gangyi Yu; Shuo Wang; Wei Liu; Yongjian Xia; Yuchen Guo; Xiaolu Chen; Xueping Wei; Ao Chen; Zehua Lv; Chao Lu; Junbo Zhang; Rong Wan (Journal of Marine Science and Engineering, 2026)
Nuclear power serves as an efficient, clean, and low-carbon energy source that constitutes a significant component of the energy portfolio in numerous countries. Most nuclear power plants are predominantly situated in coastal regions, utilizing seawater as the ultimate heat sink for their cooling systems. Real-time monitoring of marine organism dynamics near water intakes is essential to mitigate the risk of unit shutdowns triggered by outbreaks of disaster-causing organisms (DCOs). This study employed LiveScope scanning sonar videos captured near the Ningde Nuclear Power Plant to develop a dataset for detecting the light spot area of the DCOs. We proposed a directionally optimized model, Bio-YOLO v7, which significantly enhances the detection of small targets in sonar images. The Bio-YOLO v7 model achieved precision, recall, and average precision rates of 85.29%, 83.28%, and 81.49%, respectively, demonstrating superior performance in identifying DCOs near the intakes of nuclear power plant. The light spot size of the DCOs exhibited significant periodic variations, serving as a crucial indicator for forecasting outbreak events.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Novel 2-aminothiazole derivatives incorporating 9-alkyl purine moiety: design, synthesis, crystal structure, and bioactivity evaluation - Song Bai; Suran Wan; Miao Li; Rong Wu; Shouying Tang; Fang Wang; Lijun Chen; Xiaokang Lv; Xian Wei; Shuang Feng; Miaohe Zhang (Molecular Diversity, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Iron-doped biocarriers enhanced nitrogen removal from saline wastewater in an unplanted constructed wetland-microbial electrolytic cell system - Longqiang Yi; Changyuan Liu; Xinyu Rong; Kexin Li; Ruina Zhang; Xin Su; Xinting Mu; Li Wan; Yinghai Wu; Rui Han (Journal of Environmental Management, 2025)

Synergistic effects of biochar and E. coli on reducing cadmium bioavailability and improving soil fertility through enhanced bacterial-fungal interactions - Quan Chen; Rongrong Lin; Wan-Rong Zhang; Yafeng Wang; Yanqing Xiong; Pengfei Wang; Yu Huang; Min Wu; Peng Yi; Bo Pan (Journal of Hazardous Materials, 2025)

Electron beam irradiation inhibits high-moisture rice quality deterioration during storage - Dongmin Li; Jiali Xing; Pei Wang; Li Wang; Yuwei Zhang; Rong He; Dan Ouyang; Ying Wan; Xiaohu Luo (Journal of Cereal Science, 2025)

Integrative Approaches Identify Genetic Determinants of Levodopa Induced Dyskinesia - Ying Wan; Lu Rong; Qingyuan Li; Suzhi Liu; Wentao Li; Min Ye; Weifeng Luo; Anmu Xie; Jingsong Shao; Dengjun Guo; Xiaoping Zhang; Kezhong Zhang; et al. (Molecular Neurobiology, 2025)

Overexpression of the Nitraria sibirica Pall. H+-pyrophosphatase gene NsVP1 improves Arabidopsis salt tolerance - Xihong Wan; Xiuyan Yang; Rongfeng Duan; Rong Li; Yongxin You; Huaxin Zhang; Shuaihui Zhang; Pengyu Ying; Huilong Zhang (Plant Science, 2025)

Enhanced ecological risks of pollutant-adsorbed engineered environmental particles to soil microorganisms - Quan Chen; Yue Zhang; Wan-Rong Zhang; Yu Huang; Min Wu; Hong-Zhe Li; Yi-Yue Zhang; Yi-Fei Wang; Dong Zhu; Philippe Frangois-Xavier Corvini; Bo Pan (Chemical Engineering Journal, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Investigation of antibacterial activity and mechanism of action: Design and synthesis of coumarin derivatives containing sulfonamide groups - Song Bai; Miaohe Zhang; Miao Li; Suran Wan; Fang Wang; Shouyin Tang; Lijun Chen; Xian Wei; Rong Wu (Phytochemistry Letters, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Evolution of Indian monsoon precipitation and vegetation dynamics in the Bay of Bengal region since the last glacial period - Ananna Rahman; Chuanxiu Luo; Md Hafijur Rahaman Khan; Sui Wan; Yiping Yang; Haicheng Wei; Rong Xiang; Lanlan Zhang; Jianguo Liu; Xiang Su; Yun Huang (Quaternary Science Reviews, 2025)

Effect of egg white on the structure and properties of starch in wheat noodles - Jinyi Xu; Shangyuan Sang; Jinye Zhang; Jiali Xing; Rong He; Fuxing Xu; Guanghui Fang; Dan Ouyang; Ying Wan; Xiaohu Luo (Journal of Cereal Science, 2025)

ADAMDEC1 promotes cervical squamous cell carcinoma by enhancing the JAK/STAT signaling pathway through modulation of TYMP - Beibei Wang; Qingsong Zhang; Lihua Wang; Huiwen Su; Li Zhou; Rong Zhang; Qiangkun Wan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Improving forecast of “21.7” Henan extreme heavy rain by assimilating high spatial resolution GNSS ZTDs - Mengjie Liu; Yidong Lou; Weixing Zhang; Rong Wan; Zhenyi Zhang; Zhikang Fu; Xiaohong Zhang (Atmospheric Research, 2025)

Optimizing enzymatic bioreactors: The role of mass transfer in enhancing catalytic efficiency and stability - Dan Wang; Hao Zhang; Yukun Wang; Manuel Pinelo; Rosalinda Mazzei; Rong Fan; Yinhua Wan; Jianquan Luo (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Radiocarbon constraints on North Indian deep ocean ventilation and deglacial carbon dioxide release - Sui Wan; Yan Du; Lanlan Zhang; Liang Yi; Haowen Dang; Xiang Su; Jianguo Liu; Yiping Yang; Haoyin Wang; Rong Xiang (Quaternary Science Reviews, 2025)

Analysis of factors influencing microseismic detection and location in shale gas extraction areas of western Hubei - Wan-peng Hao; Li-fen Zhang; Yan-nan Zhao; Rong-ying Zheng; Wei-bing Qin; Jing-gang Li (Applied Geophysics, 2025)

Effect of electron beam irradiation on edible quality maintenance of high moisture rice grains - Dongmin Li; Ying Wan; Jinye Zhang; Yuwei Zhang; Rong He; Sangyuan Sang; Jiali Xing; Xiaohu Luo (Journal of Cereal Science, 2025)

A Meta‐Analysis of Bycatch Mitigation Methods for Sea Turtles Vulnerable to Swordfish and Tuna Longline Fisheries - Hao Yan; Cheng Zhou; Eric Gilman; Jie Cao; Rong Wan; Fan Zhang; Jiangfeng Zhu; Liuxiong Xu; Liming Song; Xiaojie Dai; Siquan Tian (Fish and Fisheries, 2025)
Fisheries bycatch poses one of the most significant threats to sea turtles. Although various methodologies have been developed to mitigate sea turtle bycatch in swordfish and tuna longline fisheries, the effectiveness and interactions remain uncertain. In this study, we conducted a comprehensive meta‐analysis, encompassing 41 studies focused on sea turtles and 36 studies on tunas, swordfish and sharks, all derived from well‐controlled experimental research in swordfish and tuna longline fisheries. The objective was to systematically evaluate the relative effectiveness of species‐specific mitigation strategies for sea turtles, particularly examining the impact of circle hooks and fish bait as alternatives to conventional longline fishing practices. While a nuanced hierarchy, characterised by species‐specific patterns, was observed among the mitigation measures, circle hooks demonstrated great promise in reducing bycatch of loggerhead, olive ridley and leatherback turtles, with minimal impact on the catch rates of tuna, swordfish and sharks. We highlighted the broader applicability of fish bait in minimising sea turtle bycatch, noting that the effectiveness of bait may overlap with that of hooks, potentially making the additional benefits of the hooks less evident. The study also revealed regional variations in the effectiveness of these methods, emphasising the need for more detailed data collection. Given current data limitations that restrict extensive meta‐analyses, a series of small‐sample studies with promising innovations, exemplified by circle hooks with a wire appendage and blue‐white lights, necessitates in‐depth investigation and field tests.

A Study on the Extraction of Satellite Image Information for Two Types of Coastal Fishery Facility Fish Cages and Rafts Influenced by Clouds and Vessels - Ao Chen; Jialu Yu; Junbo Zhang; Gangyi Yu; Rong Wan (Journal of Marine Science and Engineering, 2024)
Research on the extraction of satellite information for the areas of coastal fish cages and rafts is important to quickly grasp the pattern and structure of the coastal fishery aquaculture industry. This study proposes a multi-feature and rule-based object-oriented image classification (MROIC) model, integrating spatial-spectral enhancement techniques with object-based image analysis classification methods. The MROIC model enhances spectral information by constructing ratio bands alongside principal component analysis, subsequently employing rule sets, edge detection algorithms, and comprehensive algorithmic merging techniques. It is applicable to satellite image classification tasks in complex environments, including influence of clouds and vessels. The information of fish cage and raft facilities is extracted via the MROIC model on the southwest coast of Xiapu County, Fujian Province, as an example. The results showed that the MROIC model attained an average total classification accuracy of 90.43% and a Kappa coefficient of 0.80. Extracting the area of fisheries facilities under the influence of clouds and vessels can provide better extraction accuracy and lower omission error. The MROIC model proposed in this study demonstrates high extraction accuracy and strong applicability, offering technical support for government planning in fishery facility areas and aiding in the risk assessment and management efficiency of fishery facility insurance.

Invisible hazards: Exploring neonicotinoid contamination and its environmental risks in urban parks across China - Yongfeng Deng; Ruqin Shen; Xue Zhang; Yang Li; Xingguo Chen; Rong-Rong He; Hao Tian; Shuqin Tang; Xiang Luo; Jing Li; Wan-Yang Sun; Hongli Tan (Science of The Total Environment, 2024)

Design and modeling of an eco-friendly anchored fish aggregating device with artificial reef subjected to wave and current - Tongzheng Zhang; Wenhua Zhao; Cheng Zhou; Fenfang Zhao; Rong Wan (Ocean Engineering, 2024)

Evaluating the hydrodynamic characteristics and shape configuration of fine-mesh nettings for sampling nets - Zhiqiang Liu; Fuxiang Hu; Rong Wan; Tongzheng Zhang; Yucheng Wang; Shaojian Guo; Cheng Zhou (Ocean Engineering, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

BaP/BPDE exposure causes human trophoblast cell dysfunctions and induces miscarriage by up-regulating lnc-HZ06-regulated IL1B - Jiarong Guo; Jingsong Zhao; Peng Tian; Zhongyan Xu; Rong Wang; Weina Chen; Xiaoqing Wang; Shukun Wan; Yang Yang; Huidong Zhang (Journal of Hazardous Materials, 2024)

Difunctional POM-based artificial leaf with directed charge transfer to promote photosynthetic overall reaction - Huafeng Li; Yanan Qu; Jiayi Zhang; Kang Bu; Shiliang Heng; Shanshan Zhang; Jianzhong Guo; Bing Li; Rong Wan; Pengtao Ma; Liqun Bai (Chemical Engineering Journal, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Numerical Investigation into the Hydrodynamic Performance of a Biodegradable Drifting Fish Aggregating Device - Tongzheng Zhang; Fenfang Zhao; Rong Wan (Journal of Marine Science and Engineering, 2024)
Drifting fish aggregating devices (DFADs) can significantly enhance fishing efficiency and capability. Conventional drifting devices are prone to degradation in harsh marine environments, leading to marine waste or pollution. In this study, we develop a biodegradable DFAD (Bio-DFAD) to minimise negative impacts on marine ecology. To investigate the hydrodynamic performance of the proposed device, numerical modelling involving the unsteady Reynolds-averaged Navier–Stokes equation has been conducted, in which a realisable k–ε model is applied to consider the turbulence effect. The response amplitude operators, which are key parameters for design, are obtained for heave and pitch motions. The hydrodynamic performance is found to be sensitive to the relative length, relative diameter, and wave steepness, but they are less sensitive to the relative current velocity. This work provides some scientific insights for practical applications.

PANI/GO and Sm co-modified Ti/PbO2 dimensionally stable anode for highly efficient amoxicillin degradation: Performance assessment, impact parameters and degradation mechanism - Zeyi Wang; Luyao Zhang; Rong Su; Lu Yang; Feng Xiao; Lichuan Chen; Ping He; Dingming Yang; Yali Zeng; Yun Zhou; Ying Wan; Bin Tang (Journal of Environmental Management, 2024)

Numerical Modelling of the Hydrodynamic Performance of Biodegradable Drifting Fish Aggregating Devices in Currents - Tongzheng Zhang; Junbo Zhang; Qinglian Hou; Gangyi Yu; Ao Chen; Zhiqiang Liu; Rong Wan (Journal of Marine Science and Engineering, 2024)
Fish Aggregating Devices (FADs) are essential supplementary structures used in tropical tuna purse-seine fishing. They are strategically placed to attract tuna species and enhance fishing productivity. The hydrodynamic performance of FADs has a direct effect on their structural and environmental safety in the harsh marine environment. Conventional FADs are composed of materials that do not break down naturally, leading to the accumulation of waste in the ocean and potential negative effects on marine ecosystems. Therefore, this work aimed to examine the hydrodynamic performance of biodegradable drifting FADs (Bio-DFADs) in oceanic currents by numerical modelling. The Reynolds-averaged Navier–Stokes equation was used to solve the flow field and discretized based on the realizable k-ε turbulence model, employing the finite volume method. A set of Bio-DFADs was developed to assess the hydrodynamic performance under varying current velocities and attack angles, as well as different balsa wood diameters and sinker weights. The results indicated that the relative current velocity significantly affected the relative velocity of Bio-DFADs. The relative length of the raft significantly affected both the relative velocity and the relative wetted area in a pure stream. Finally, the diameter of the balsa wood affected the drift velocity, and the sinker’s relative weight affected the hydrodynamic performance of the Bio-DFADs.

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Environmental copper exposure, placental cuproptosis, and miscarriage - Jingsong Zhao; Zhongyan Xu; Xiaoqing Wang; Shukun Wan; Weina Chen; Wenxin Huang; Manli Wang; Rong Wang; Huidong Zhang (Environmental Pollution, 2024)

Numerical Study of the Hydrodynamic Response of Biodegradable Drifting Fish Aggregating Devices in Regular Waves - Tongzheng Zhang; Zhiqiang Liu; Junbo Zhang; Xing Su; Junlin Chen; Rong Wan (Fishes, 2024)
Fish-aggregating devices play a significant role in tuna purse fisheries. The severe marine environment and the large number of non-biodegradable fish-aggregating devices impact structural safety and cause marine litter. Therefore, hydrodynamic performance and the use of biodegradable materials are crucial issues for ensuring the sustainability of fish-aggregating devices. In this study, a type of virtual biodegradable drifting fish-aggregating device (Bio-DFAD) was designed. Numerical simulations were conducted to investigate the motion responses and relative velocities of Bio-DFADs in regular waves (first- and fifth-order waves). The numerical model was applied based on unsteady Reynolds-averaged Navier–Stokes equations with the realizable k–ε model. For different scenarios of modeling, various conditions were modeled, including the relative length, wave steepness, and diameter of the balsa wood, to analyze their effects on the hydrodynamic response of the Bio-DFADs. The results indicated that the increased relative length, wave steepness, and diameter of balsa wood had a significant influence on the motion response amplitude operators (RAOs) and relative velocity of Bio-DFADs. The results suggested that a relative length (LF/B = 1.5) and smaller diameter (DF = 30 mm) were recommended for fewer motion responses and relative velocity. The obtained results provide insight for practical engineering applications of the hydrodynamic design of Bio-DFADs.

Polystyrene nanoplastics inhibit beige fat function and exacerbate metabolic disorder in high-fat diet-fed mice - Lina Zhang; Baocheng Wan; Jiangfei Zheng; Liwei Chen; Ye Xuan; Rong Zhang; Zhuo Chen; Cheng Hu; Yi Zhang; Chonghuai Yan (Science of The Total Environment, 2024)

Review of the Accuracy of Satellite Remote Sensing Techniques in Identifying Coastal Aquaculture Facilities - Ao Chen; Zehua Lv; Junbo Zhang; Gangyi Yu; Rong Wan (Fishes, 2024)
The predominant form of aquaculture is the facility fishery, which is also subject to significant impacts from marine disasters. Conducting research on the extraction of facility fishery areas based on remote sensing technology is crucial to efficiently comprehending the configuration of coastal culture patterns and to establishing scientifically sound plans for managing and administering these areas. The extensive dispersion of facility fishery areas in coastal regions poses a challenge to the conduction of comprehensive field surveys. The utilization of satellite remote sensing images for information extraction has emerged as a significant area of research in the fields of coastal fishery and ecological environment. This study provides a systematic description of the current research status of coastal fishery area extraction methods using remote sensing technology from 2000 to 2022 reported in the literature. The methods discussed include the visual interpretation method, image element-based classification, object-based classification, supervised classification, unsupervised classification, and neural network classification. The extraction accuracy of each method in the coastal facility fishery area is evaluated, and the advantages and disadvantages of these methods, as well as their limitations and existing problems, are analyzed in detail, to construct a reference framework for the investigation of the high-precision extraction of facility fishery areas from satellite remote sensing images.

Hypervirulent Klebsiella pneumoniae detection methods: a minireview - Qi-bin Zhang; Peng Zhu; Shun Zhang; Yan-jing Rong; Zuo-an Huang; Li-wan Sun; Ting Cai (Archives of Microbiology, 2023)

Evaluating the service quality of insular and coastal recreational fisheries by integration of the SERVQUAL-fuzzy Kano model and importance-performance analysis - Xinqiang Jiang; Junbo Zhang; Chenxing Yang; Rong Wan (Ocean & Coastal Management, 2023)

Solvent-freely polymerizing catechol and paraformaldehyde to nitrogen-rich carbon for high-volumetric-performance supercapacitor - Yushuai Yao; Rong Zhou; Yi Yu; Jian Chen; Cheng Du; Yan Zhang; Tao Long; Liu Wan; Qiuyue Wang; Mingjiang Xie (Chemical Engineering Journal, 2023)

Host insect specificity and interspecific competition drive parasitoid diversification in a plant–insect community - Ai‐Ying Wang; Yan‐Qiong Peng; James M. Cook; Da‐Rong Yang; Da‐Yong Zhang; Wan‐Jin Liao (Ecology, 2023)
Ecological interactions among plants, insect herbivores, and parasitoids are pervasive in nature and play important roles in community assembling, but the codiversification of tri‐trophic interactions has received less attention. Here we compare pairwise codiversification patterns between a set of 22 fig species, their herbivorous pollinating and galling wasps, and their parasitoids. The parasitoid phylogeny showed significant congruence and more cospeciation events with host insects phylogeny than with host plants. These results suggest that parasitoid phylogeny and speciation is more closely related to their host insects than to their host plants. The pollinating wasps hosted more parasitoid species than gallers and indicated a more intense interspecific competition among parasitoids associated with pollinators. Closer matching and fewer evolutionary host shifts were found between parasitoids and galler hosts than between parasitoids and pollinator hosts. These results suggest that interspecific competition among parasitoids, rather than resource availability of host wasps, is the main driver of the codiversification pattern in this community. Therefore, our study highlights the important role of interspecific competition among high trophic level insects in plant–insect tri‐trophic community assembling.

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Molecular Hydrogen Mediates Neurorestorative Effects After Stroke in Diabetic Rats: the TLR4/NF-κB Inflammatory Pathway - Wan-Chao Yang; Ting-ting Li; Qiang Wan; Xin Zhang; Li-Ying Sun; Yu-Rong Zhang; Pei-Chen Lai; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)
Diabetes is an independent risk factor for stroke and amplifies inflammation. Diabetic stroke is associated with a higher risk of death and worse neural function. The identification of effective anti-inflammatory molecules with translational advantages is particularly important to promote perioperative neurorestorative effects. Applying molecular hydrogen, we measured blood glucose levels before and after middle cerebral artery occlusion (MCAO), 48-h cerebral oedema and infarct volumes, as well as 28-day weight, survival and neurological function. We also measured the levels of TLR4, NF-κB p65, phosphorylated NF-κB p65, catecholamines, acetylcholine and inflammatory factors. All measurements comprehensively showed the positive effect and translational advantage of molecular hydrogen on diabetic stroke. Molecular hydrogen improved the weight, survival and long-term neurological function of rats with diabetic stroke and alleviated changes in blood glucose levels before and after middle cerebral artery occlusion (MCAO), but no difference in circadian rhythm was observed. Molecular hydrogen inhibited the phosphorylation of NF-κB and significantly reduced inflammation. Molecular hydrogen mediates neurorestorative effects after stroke in diabetic rats. The effect is independent of circadian rhythms, indicating translational advantages. The molecular mechanism is related to the TLR4/NF-κB pathway and inflammation. Graphical abstract Molecular hydrogen (H 2 ) affects outcomes of ischemic stroke with diabetes mellitus (DM).

Corrigendum to “Promotional effects of calcination temperature and H2O on the catalytic activity of Al-substituted MnAlO catalysts for low-temperature acetone oxidation” [Chemosphere 301 (2022) 134722] - Wan-Peng Zhang; Kun Wu; Junyi Zhao; Jun He; Leiping Wang; Hang Xiao; Jian-Bing Guo; Jian-Rong Li (Chemosphere, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

The loss of Halloween gene function seriously affects the development and reproduction of Diaphorina citri (Hemiptera: Liviidae) and increases its susceptibility to pesticides - Cong Zhang; Bin Wan; Meng-Ru Jin; Jing Wang; Tian-Rong Xin; Zhi-Wen Zou; Bin Xia (Pesticide Biochemistry and Physiology, 2023)

Detection and Identification of Fish Skin Health Status Referring to Four Common Diseases Based on Improved YOLOv4 Model - Gangyi Yu; Junbo Zhang; Ao Chen; Rong Wan (Fishes, 2023)
A primary problem affecting the sustainable development of aquaculture is fish skin diseases. In order to prevent the outbreak of fish diseases and to provide prompt treatment to avoid mass mortality of fish, it is essential to detect and identify skin diseases immediately. Based on the YOLOv4 model, coupled with lightweight depthwise separable convolution and optimized feature extraction network and activation function, the detection and identification model of fish skin disease is constructed in this study. The developed model is tested for the diseases hemorrhagic septicemia, saprolegniasis, benedeniasis, and scuticociliatosis, and applied to monitor the health condition of fish skin in deep-sea cage culture. Results show that the MobileNet3-GELU-YOLOv4 model proposed in this study has an improved learning ability, and the number of model parameters is reduced. Compared to the original YOLOv4 model, its mAP and detection speed increased by 12.39% and 19.31 FPS, respectively. The advantages of the model are its intra-species classification capability, lightweight deployment, detection accuracy, and speed, making the model more applicable to the real-time monitoring of fish skin health in a deep-sea aquaculture environment.

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

QNE1 is a key flowering regulator determining the length of the vegetative period in soybean cultivars - Zhengjun Xia; Hong Zhai; Yanfeng Zhang; Yaying Wang; Lu Wang; Kun Xu; Hongyan Wu; Jinglong Zhu; Shuang Jiao; Zhao Wan; Xiaobin Zhu; Yi Gao; et al. (Science China Life Sciences, 2022)

Optimization of the Hydrodynamic Performance of a Double-Vane Otter Board Based on Orthogonal Experiments - Lei Wang; Xun Zhang; Rong Wan; Qingchang Xu; Guangrui Qi (Journal of Marine Science and Engineering, 2022)
An orthogonal experiment was conducted to study the effects of the aspect ratio, camber of the fore wing, and gap ratio of front and rear wing panels on the hydrodynamic performance of double-vane otter boards. The design of the orthogonal experiment comprised three factors (each having three levels), namely the aspect ratio (1.0, 1.5, and 2.0), camber (0.12, 0.14, and 0.16), and gap ratio (0.25, 0.30, and 0.35), the drag coefficient Cx and the lift coefficient Cy of nine otter board models obtained in a wind tunnel experiment, and the lift–drag ratio K obtained by calculation. The lift–drag ratio for a working angle of attack of 30° was selected as the inspection index, and the experimental data were analyzed in an orthogonal design-direct analysis. Analysis of each factor revealed that the optimal level combination of factors was A3B3C3 and that the decreasing order of the effects of the factors was A (aspect ratio) > B (gap ratio) > C (camber). The orthogonal experiment thus obtained an optimal otter board in terms of the aspect ratio (2.0), fore wing camber (0.16), and gap ratio (0.35), with the aspect ratio having the greatest effect on performance. The hydrodynamic performances of the otter board with the optimized structure and another otter board model were compared in numerical simulation, which verified the correctness of the analysis results. The experimental results provide a reference for the optimal design of the double-vane otter board.

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

Sampling Designs for Monitoring Ichthyoplankton in the Estuary Area: A Case Study on Coilia mystus in the Yangtze Estuary - Xiangyu Long; Rong Wan; Zengguang Li; Dong Wang; Pengbo Song; Fan Zhang (Frontiers in Marine Science, 2022)
A fishery-independent survey can provide detailed information for fishery assessment and management. However, the sampling design for the survey on ichthyoplankton in the estuary area is still poorly understood. In this study, we developed six stratified schemes with various sample sizes, attempting to find cost-efficient sampling designs for monitoring Coilia mystus ichthyoplankton in the Yangtze Estuary. The generalized additive model (GAM) with the Tweedie distribution was used to quantify the “true” distribution of C. mystus eggs and larvae, based on the data from the fishery-independent survey in 2019–2020. The performances of different sampling designs were evaluated by relative estimation error (REE), relative bias (RB), and coefficient of variation (CV). The results indicated that appropriate stratifications with intra-stratum homogeneity and inter-stratum heterogeneity could improve precision. The stratified schemes should be divided not only between the North Branch and South Branch but between river and sea. No less than two stratifications in the South Branch could also get better performance. The sample sizes of 45–55 were considered as the cost-efficient range. Compared to other monitoring programs, monitoring ichthyoplankton in the estuary area required a more complex stratification and a higher resolution sampling. The design ideology and optimization methodology in our study would provide references to sampling designs for ichthyoplankton in the estuary area.

Application of Feature Point Matching Technology to Identify Images of Free-Swimming Tuna Schools in a Purse Seine Fishery - Qinglian Hou; Cheng Zhou; Rong Wan; Junbo Zhang; Feng Xue (Journal of Marine Science and Engineering, 2021)
Tuna fish school detection provides information on the fishing decisions of purse seine fleets. Here, we present a recognition system that included fish shoal image acquisition, point extraction, point matching, and data storage. Points are a crucial characteristic for images of free-swimming tuna schools, and point algorithm analysis and point matching were studied for their applications in fish shoal recognition. The feature points were obtained by using one of the best point algorithms (scale invariant feature transform, speeded up robust features, oriented fast and rotated brief). The k-nearest neighbors (KNN) algorithm uses ‘feature similarity’ to predict the values of new points, which means that new data points will be assigned a value based on how closely they match the points that exist in the database. Finally, we tested the model, and the experimental results show that the proposed method can accurately and effectively recognize tuna free-swimming schools.

The Non-stationary Environmental Effects on Spawning Habitat of Fish in Estuaries: A Case Study of Coilia mystus in the Yangtze Estuary - Dong Wang; Rong Wan; Zengguang Li; Junbo Zhang; Xiangyu Long; Pengbo Song; Lu Zhai; Shuo Zhang (Frontiers in Marine Science, 2021)
The estuarine areas provide necessary spawning habitat, nursing habitat, and migratory for a variety of fishes and the environmental conditions are of significant heterogeneity. Coilia mystus is the key commercial fish that spawns in the Yangtze Estuary and the yield has declined sharply in the past 30 years. In order to understand the spawning habitat selection mechanism of C. mystus , the geographically weighted regression (GWR) model was applied to explore the non-stationary effect of environmental variables [e.g., the sea surface temperature (SST) and the sea surface salinity (SSS)] and geographical variables [e.g., the distance to the coast (DTC) and the depth (DEP) of water] on the egg density distribution of C. mystus . The data were derived from the spring and summer ichthyoplankton surveys carried out from 2019 to 2020 in the Yangtze Estuary, China. The GWR model results showed that the key variables in different seasons had spatial non-stationary effects on the distribution of spawning habitat of C. mystus , which were mainly caused by regional rise in temperature and saltwater intrusion of the South Branch. In the spring, the SSS, the DTC, and the DEP were the main impact factors and saltwater intrusion in the South Branch might lead to the trend that the spawning habitat moved further upstream to the Changxing Island. The SST was most important in the summer and the relatively lower SST was more crucial in the spawning habitat selection than the DTC and the DEP. The GWR model performed well in the study of C. mystus potential spawning habitat in the Yangtze Estuary. We recommend that more attention should be paid in regional variation of environmental factors to explore fish potential spawning habitat in the estuarine areas.

Reduction of mussel metamorphosis by inactivation of the bacterial thioesterase gene via alteration of the fatty acid composition - Xiao-Meng Hu; Junbo Zhang; Wen-Yang Ding; Xiao Liang; Rong Wan; Sergey Dobretsov; Jin-Long Yang (Biofouling, 2021)

Improvement on the Effectiveness of Marine Stock Enhancement in the Artificial Reef Area by a New Cage-Based Release Technique - Junbo Zhang; Yufeng He; Zhixing Guo; Shuheng Ji; Shuo Zhang; Yanli Tang; Huaxiang Sheng; Rong Wan; Daisuke Kitazawa (Journal of Ocean University of China, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Molecular Characterization of Hsp47 in Grass Carp (Ctenopharyngodon idella) and Its Correlation with Type I Collagen in Response to Fish Aerobic Exercise - Xiao Liang; Ying Wan; Zhiyuan Shen; Yanmei Liu; Dapeng Li; Li Li; Rong Tang; Xi Zhang (Fishes, 2021)
Heat shock protein 47 (Hsp47) is a collagen-specific molecular chaperone that is indispensable for molecular maturation of collagen. In this study, hsp47 and hsp47-like cDNAs were cloned and characterized in grass carp (Ctenopharyngodon idella). The cDNAs were 1212 and 1218 base pairs long, respectively, and included an open reading frame encoding 403 and 405 amino acids. The molecular phylogeny based on the deduced amino acid sequences indicated that the correct sequences of the hsp47 and hsp47-like cDNA were obtained and the deduced proteins clustered distinctly into teleost clades. Primary structure analysis and characterization of Hsp47 and Hsp47-like shared the basic structure and biofunctions of Hsp47 in vertebrates. The spatial pattern of gene expression revealed that hsp47 and hsp47-like were relatively ubiquitous in different tissues and highly expressed in heart and skin. The expression levels of hsp47 and hsp47-like and type I collagen mRNAs varied similarly in different tissues. Type I collagen content increased significantly with the increase of water velocity in the muscle of grass carp in response to aerobic exercise. Among the gene expression changes of hsp47, hsp47-like, col1a1 and col1a2 in muscle that occurred in response to aerobic exercise, the change of type I collagen was most strongly correlated with hsp47 expression. Additionally, col1a1 showed the highest correlation with hsp47-like and col1a2 showed the highest correlation with hsp47. These findings suggest that grass carp Hsp47 and Hsp47-like are closely related to type I collagen synthesis. This study firstly suggests fish aerobic exercise can improve type I collagen content and Hsp47 gene expression in muscle of grass carp.

Review of Estimating Trophic Relationships by Quantitative Fatty Acid Signature Analysis - Junbo Zhang; Chonglan Ren; Hu Zhang; Fang Yin; Shuo Zhang; Rong Wan; Daisuke Kitazawa (Journal of Marine Science and Engineering, 2020)
The dynamic predator–prey relations in the food web are vital for understanding the function and structure of ecosystems. Dietary estimation is a research hotspot of quantitative ecology, providing key insights into predator–prey relationships. One of the most promising approaches is quantitative fatty acid signature analysis (QFASA), which is the first generation of statistical tools to estimate the quantitative trophic predator–prey relationships by comparing the fatty acid (FA) signatures among predators and their prey. QFASA has been continuously widely applied, refined and extended since its introduction. This article reviewed the research progress of QFASA from development and application. QFASA reflects the long-term diet of predator, and provides the quantitative dietary composition of predator, but it is sensitive to the metabolism of predator. The calibration coefficients (CCs) and the FA subset are two crucial parameters to explain the metabolism of predators, but the incorrect construction or improper use of CCs and the FA subset may cause bias in dietary estimation. Further study and refinement of the QFASA approach is needed to identify recommendations for which CCs and subsets of FA work best for different taxa and systems.

Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - Jie Lan; Qibing Lin; Chunlei Zhou; Yakun Ren; Xi Liu; Rong Miao; Ruonan Jing; Changling Mou; Thanhliem Nguyen; Xingjie Zhu; Qian Wang; Xin Zhang; et al. (Plant Molecular Biology, 2020)

Optimized Algorithm for Processing Outlier of Water Current Data Measured by Acoustic Doppler Velocimeter - Chunyi Zhong; Fang Yin; Junbo Zhang; Shuo Zhang; Rong Wan; Daisuke Kitazawa (Journal of Marine Science and Engineering, 2020)
In the process of pond culture, the usage of an aeration device can increase dissolved oxygen density and form a decent circulation which facilitates the collection of sludge. Acoustic Doppler Velocimeter (ADV) has been widely used to monitor the flow velocity, however, factors such as bubbles and suspended particles can affect the correlation coefficient and signal-to-noise ratio of ADV, which leads to the existence of outliers in velocity data. This study constructs the three-dimensional rousseeuw phase-space (3DRPS) method by optimizing the phase space threshold method and robust estimation method through two-step filtering and three-dimensional simultaneous measurement, where the outliers close to the real value can be detected more accurately and the iterative process can be reduced more effectively. The results show that the detection rate of the optimized 3DRPS method is approximately 99%. It is a promising method that effectively improves the accuracy of outlier detection and greatly reduces the phenomenon of over processing.

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Circular RNA hsa_circ_0002052 promotes osteosarcoma via modulating miR-382/STX6 axis - Ping-rong Zhang; Jing Ren; Jian-shan Wan; Rong Sun; Ying Li (Human Cell, 2020)

The effects of mesoscale oceanographic structures and ambient conditions on the catch of albacore tuna in the South Pacific longline fishery - Cheng Zhou; Pingguo He; Liuxiong Xu; Pascal Bach; Xuefang Wang; Rong Wan; Hao Tang; Yu Zhang (Fisheries Oceanography, 2020)
Albacore tuna ( Thunnus alalunga ) exhibit patchy concentrations associated with biological process at a wide range of spatial scales, resulting in variations in their catchability by fishing gears. Here, we investigated the association of catch variation for pelagic longlines in the South Pacific Ocean with oceanographic mesoscale structures (in horizontal dimension) and ambient conditions (in vertical dimension). The distribution of albacore tuna as indicated by catch per unit effort (CPUE) of longlines was significantly related to the presence of mesoscale structures, with higher CPUE found at locations closer to thermal fronts and with greater gradient magnitudes, as well as areas marked by peripheral contour line of the anticyclone indicated by Sea Surface Height Anomalies ~0.05 m. Surface mesoscale current velocity had the negative effect on the catch, probably as a result of decreased catchability by shoaling the hook depth. Vertical distribution of albacore in the survey region of South Pacific Ocean was hardly restricted by ambient temperature and oxygen concentration, though effect of ambient temperature was relevant and showed a negatively linear correlation with CPUE at the range of 20–24°C. On the contrary, albacore distribution was evidently dominated by the water depth and showed strong preference on water depth of 200 m, which was likely a representative feeding layer. The presence of prey resources and their accessibility by albacore revealed by mesoscale structures in the biological and physical processes, and catchability determined by the location of the baited hooks comprehensively contribute to the variability of catch.

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Molecular cloning and characterization of genes related to the ethylene signal transduction pathway in pomegranate (Punica granatum L.) under different temperature treatments - Rong Huang; Wei Li; Xiao-Wan Guan; Biao Xie; Shui-Ming Zhang (Journal of Biosciences, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Optimized culture medium for the production of flavonoids from Orostachys cartilaginea V.N. Boriss. callus cultures - Wan Bo Zhang; Xuan Chun Piao; Jin Rong Li; Ying Hua Jin; Mei Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Slow-release nitrogen fertilizers can improve yield and reduce Cd concentration in pakchoi (Brassica chinensis L.) grown in Cd-contaminated soil - Ran-Ran Zhang; Yue Liu; Wan-Lei Xue; Rong-Xin Chen; Shao-Ting Du; Chong-Wei Jin (Environmental Science and Pollution Research, 2016)

Metagenomic analysis shows diverse, distinct bacterial communities in biofilters among different marine recirculating aquaculture systems - Zhitao Huang; Rong Wan; Xiefa Song; Ying Liu; Eric Hallerman; Dengpan Dong; Jieming Zhai; Hesen Zhang; Liyuan Sun (Aquaculture International, 2016)

Population structure of Japanese Spanish mackerel Scomberomorus niphonius in the Bohai Sea, the Yellow Sea and the East China Sea: evidence from random forests based on otolith features - Chi Zhang; Zhenjiang Ye; Zengguang Li; Rong Wan; Yiping Ren; Shuozeng Dou (Fisheries Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Optimization of stratification scheme for a fishery-independent survey with multiple objectives - Binduo Xu; Yiping Ren; Yong Chen; Ying Xue; Chongliang Zhang; Rong Wan (Acta Oceanologica Sinica, 2015)

Inside out: high-efficiency plant regeneration and Agrobacterium-mediated transformation of upland and lowland switchgrass cultivars - Yan-Rong Liu; Hui-Fang Cen; Jian-Ping Yan; Yun-Wei Zhang; Wan-Jun Zhang (Plant Cell Reports, 2015)

AngiotensinII induces HuR shuttling by post-transcriptional regulated CyclinD1 in human mesangial cells - Yu Che; Liu Yi; Javed Akhtar; Chen Bing; Zhang Ruiyu; Wan Qiang; Wang Rong (Molecular Biology Reports, 2014)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Isolation and identification of a non-haemagglutinating strain of rabbit hemorrhagic disease virus from China and sequence analysis for the VP60 Gene - Lang Tian; Juan Liao; Jian-wen Li; Wan-rong Zhou; Xia-lan Zhang; Hong-ning Wang (Virus Genes, 2007)

Characterizing and estimating rice brown spot disease severity using stepwise regression, principal component regression and partial least-square regression - Zhan-yu Liu; Jing-feng Huang; Jing-jing Shi; Rong-xiang Tao; Wan Zhou; Li-li Zhang (Journal of Zhejiang University-SCIENCE B, 2007)